Pemanfaatan Media Komik Digital: Sarana Sosialisasi Ajaran Islam Terhadap Jasa Joki Tugas Pelajar - Hanbali, Ayala Paska (JIE (Journal of Islamic Education), 2023)
To find out digital comic media as a means of disseminating Islamic views on task jockey services among students; to find out the design of digital comic media as a means of disseminating Islamic views on task jockey services among students; to find out digital comic media products as a means of disseminating Islamic views on task jockey services among students; and to find out the assessment of digital comic media as a means of disseminating Islamic views on task jockey services among students. The research method used is development research. The type of development research used is Design and Development (D&D). This comic product is worthy of being used as a means of disseminating Islamic views on the service of task jockeys among students. Comics that are made are like comics in general, which prioritize illustrations in them and also provide messages and meanings that will be conveyed by the creators. The results of the validation on Instagram got 86 likes and based on the responses given that the content submitted was quite good, which means that the material presented was appropriate, but readers experienced confusion from the sequence of conversations in the comic. According to one of the teachers, the comics that have been made are good, especially since these comics are very colorful which will attract the interest of teenagers.